Assessment of sagittal lip position and some affecting factors in a sample of Iraqi adults (Mustansiria Dental Journal, 2018)
This study aimed to determine the sagittal lip position and some of the factorsaffecting it regarding the gender differences, and their correlations in a sample of Iraqiadults.Sixty two participants (37 females and 25 males) collected among dental studentshaving Cl I skeletal and occlusal relations and full permanent dentition regardless thethird molars were chosen for this study. Each person was subjected to clinicalexamination and digital true lateral cephalometric radiograph. The radiographs wereanalyzed by using AutoCAD 2007 computer program to measure the sagittal lipposition using the soft tissue analyses of Steiner, Burstone, Ricketts, Sushner,Holdaway, and Merrifield. Descriptive statistics were obtained from themeasurements of both genders; independent samples t-test was performed to evaluatethe gender differences and Pearson’s correlation coefficient test was used to find thecontributing factors to the sagittal lip position.Sagittal jaw angles were significantly higher in males than females, while verticaljaw angle was higher in females. Lower incisors showed slight proclination in bothgenders. The mean values of H-angle and revised H-angle in males were nonsignificantlyhigher than that of females, while the mean value of Z-angle was nonsignificantlyhigher in females. Upper and lower lips thickness mean values weresignificantly higher in males. Females had non-significantly more projected nosecompared to males. Regarding the sagittal lip position, upper and lower lipmeasurements were non-significantly higher in males than females in Ricketts,Steiner, Burstone, and Holdaway analyses, but it was significant in Sushner analysis,while Z-angle of Merrilfield was non-significantly higher in female sample. Pearson’scorrelation coefficient test revealed that upper and lower lip thickness wassignificantly positively correlated with sagittal lip position, while nose projection wassignificantly negatively correlated.Sagittal position values of the upper and lower lips in a sample of Iraqi adults areclose to the norms of Ricketts, Steiner, Sushner, Burstone, and Holdaway analyseswith a slight tendency of upper lip toward retrusion and lower lip toward protrusionwith the exception of that when compared with Sushner norms. In addition to the chinposition, lips thickness and nose projection are the most important factors thatinfluence the sagittal lip position and compensate for the variations in the jaw basesbetween genders.